Annual Plan 2001-2002 Volume I Scheme wise Plan Outlay National Capital Territory of Delhi - Planning Commission (Planning Commission, 2001)
Geographically, Delhi is located in the heart of northern India, surrounded by the States of Haryana and Uttar Pradesh. It covers areas of 1483 sq. kms. of which 798 sq. kms. is rural and 685 sq. kms. is urban. Due to rapid urbanisation, the rural area is diminishing gradually in Delhi and this is evident from the following table.
Planning Department, Government of National Capital Territory of Delhi